Genetic deletion or TWEAK blocking antibody administration reduce atherosclerosis and enhance plaque stability in mice - Sastre, Cristina (John Wiley & Sons Ltd, 2014)
Clinical complications associated with atherosclerotic plaques arise from luminal obstruction due to plaque growth or destabilization leading to rupture. Tumour necrosis factor ligand superfamily member 12 (TNFSF12) also known as TNF-related weak inducer of apoptosis (TWEAK) is a proinflammatory cytokine that participates in atherosclerotic plaque development, but its role in plaque stability remains unclear. Using two different approaches, genetic deletion of TNFSF12 and treatment with a TWEAK blocking mAb in atherosclerosis-prone mice, we have analysed the effect of TWEAK inhibition on atherosclerotic plaques progression and stability. Mice lacking both TNFSF12 and Apolipoprotein E (TNFSF12(−/−)ApoE(−/−)) exhibited a diminished atherosclerotic burden and lesion size in their aorta. Advanced atherosclerotic plaques of TNFSF12(−/−)ApoE(−/−) or anti-TWEAK treated mice exhibited an increase collagen/lipid and vascular smooth muscle cell/macrophage ratios compared with TNFSF12(+/+)ApoE(−/−) control mice, reflecting a more stable plaque phenotype. These changes are related with two different mechanisms, reduction of the inflammatory response (chemokines expression and secretion and nuclear factor kappa B activation) and decrease of metalloproteinase activity in atherosclerotic plaques of TNFSF12(−/−)ApoE(−/−). A similar phenotype was observed with anti-TWEAK mAb treatment in TNFSF12(+/+)ApoE(−/−) mice. Brachiocephalic arteries were also examined since they exhibit additional features akin to human atherosclerotic plaques associated with instability and rupture. Features of greater plaque stability including augmented collagen/lipid ratio, reduced macrophage content, and less presence of lateral xanthomas, buried caps, medial erosion, intraplaque haemorrhage and calcium content were present in TNFSF12(−/−)ApoE(−/−) or anti-TWEAK treatment in TNFSF12(+/+)ApoE(−/−) mice. Overall, our data indicate that anti-TWEAK treatment has the capacity to diminish proinflamatory response associated with atherosclerotic plaque progression and to alter plaque morphology towards a stable phenotype.